2005
DOI: 10.1128/jcm.43.10.5044-5047.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Cerebral Toxoplasmosis in AIDS Patients in Brazil: Importance of Molecular and Immunological Methods Using Peripheral Blood Samples

Abstract: Cerebral toxoplasmosis is the most common cerebral focal lesion in AIDS and still accounts for high morbidity and mortality in Brazil. Its occurrence is more frequent in patients with low CD4 ؉ T-cell counts. It is directly related to the prevalence of anti-Toxoplasma gondii antibodies in the population. Therefore, it is important to evaluate sensitive, less invasive, and rapid diagnostic tests. We evaluated the value of PCR using peripheral blood samples on the diagnosis of cerebral toxoplasmosis and whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
8

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 38 publications
5
74
0
8
Order By: Relevance
“…It is possible that the B antigen exerts a small influence on the adherence of T. gondii to the gastrointestinal mucosa and its contribution is obscured by the high prevalence of infection by these parasites in the Brazilian population, as well as by the molecular variability of its strains identified in Brazilian patients (35)(36)(37)(38). Moreover, the use of only female patients in this study and in the one performed in France might not be sufficient to reveal possible influences of gender in the association of the ABO blood group system with infection by T. gondii (10).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the B antigen exerts a small influence on the adherence of T. gondii to the gastrointestinal mucosa and its contribution is obscured by the high prevalence of infection by these parasites in the Brazilian population, as well as by the molecular variability of its strains identified in Brazilian patients (35)(36)(37)(38). Moreover, the use of only female patients in this study and in the one performed in France might not be sufficient to reveal possible influences of gender in the association of the ABO blood group system with infection by T. gondii (10).…”
Section: Discussionmentioning
confidence: 99%
“…Infection is asymptomatic in most individuals, whereas severe pathology and lethality due to toxoplasmosis is a common finding in congenitally infected or immunodeficient patients (Desmonts and Couvreur 1974). In addition, toxoplasmosis is one of the most common causes of infectious uveitis in both immunocompetent and immunocompromised persons (Holland 1999, Colombo et al 2005. Importantly, some studies indicate that toxoplasmic retinocoroiditis and ocular disease is frequently found in cases of acquired toxoplasmosis (Glasner et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…5,15 Recently, we reported our experience with conventional PCR assay using peripheral blood samples in patients with AIDSrelated CT, showing a sensitivity of 80% and a specificity of 98%. 7 These very divergent results can be due, at least in part, to several reasons: choice of target DNA and primers, PCR techniques, conditions and time of sample storage, and collection of blood samples before or in the first days after introduction of specific treatment. 5,15,16 It was reported that genotypes of T. gondii strains isolated from patients with ocular toxoplasmosis in Brazil were highly divergent when compared to the previously described clonal lineages from North America and Europe, suggesting more frequent sexual recombinants resulting in mixed genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…PCR and IFI methodologies were reported elsewhere. 7 For statistical analysis, the outcome variable in the present study was the diagnosis of CT. Univariate logistic regression analysis was performed to identify the independent variables that were associated with the diagnosis of CT. The list of potential variables included age, gender, prior CT, lymphocyte T-CD4+ cell count, use of CT prophylaxis at admission, positive IgG anti-T. gondii IFI, high titers of IgG anti-T. gondii IFI, and a positive PCR result for T. gondii DNA in blood samples.…”
Section: Methodsmentioning
confidence: 99%